ANALISIS KUALITAS KENYAMANAN JALUR PEDESTRIAN DI KAWASAN WISATA SANUR DENPASAR - Yolanda Chindrayani Yofee; I Ketut Mudra; Tri Anggraini Prajnawrdhi (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
Abstract : This study analyzes the quality of pedestrian comfort in the Sanur Tourism Area, Denpasar, where pedestrian paths play an important role in supporting tourism activities, social interaction, and public mobility. The purpose of this research is to evaluate the quality of pedestrian comfort and identify the factors influencing user comfort along the Sanur coastal pedestrian corridor. This study employed a qualitative descriptive approach through field observations and visual documentation conducted along a 5.8 km pedestrian corridor divided into four segments. The analysis was based on eight comfort aspects, namely circulation, climate, noise, odor, form, safety, cleanliness, and aesthetics. The results show that the level of comfort varies between segments. Segment 2 demonstrates the highest comfort level due to well-organized circulation, adequate shading, good safety, cleanliness, and strong visual aesthetics. Segments 1 and 4 show moderate comfort levels influenced by high tourist activity and coastal environmental factors. Segment 3 exhibits the lowest comfort level due to limited shading, sand intrusion, unclear circulation separation, low lighting, and weak visual elements. The findings indicate that pedestrian comfort in coastal tourism areas is influenced not only by natural beauty but also by proper spatial organization and facility managementKeyword: Pedestrian Path, Comfort, Sanur Tourism Area Abstrak: Penelitian ini menganalisis kualitas kenyamanan jalur pedestrian di Kawasan Wisata Sanur, Denpasar, yang berperan penting dalam menunjang aktivitas wisata, interaksi sosial, dan mobilitas masyarakat. Tujuan penelitian ini adalah untuk mengevaluasi kualitas kenyamanan jalur pedestrian serta mengidentifikasi faktor-faktor yang memengaruhi kenyamanan pengguna di sepanjang koridor pedestrian Pantai Sanur. Penelitian ini menggunakan pendekatan kualitatif deskriptif melalui observasi lapangan dan dokumentasi visual pada jalur pedestrian sepanjang 5,8 km yang dibagi menjadi empat segmen. Analisis dilakukan berdasarkan delapan aspek kenyamanan, yaitu sirkulasi, iklim, kebisingan, aroma, bentuk, keamanan, kebersihan, dan estetika. Hasil penelitian menunjukkan bahwa tingkat kenyamanan berbeda pada setiap segmen. Segmen 2 memiliki tingkat kenyamanan paling optimal karena didukung sirkulasi yang tertata, peneduhan yang baik, keamanan, kebersihan, dan kualitas estetika yang tinggi. Segmen 1 dan Segmen 4 berada pada tingkat kenyamanan sedang, sedangkan Segmen 3 memiliki tingkat kenyamanan terendah akibat minimnya vegetasi peneduh, masuknya pasir ke jalur, rendahnya pencahayaan, serta keterbatasan elemen visual buatan. Hasil penelitian ini menegaskan bahwa kenyamanan jalur pedestrian kawasan wisata dipengaruhi oleh faktor alam dan kualitas penataan ruang.Kata Kunci: Jalur Pedestrian, Kenyamanan, Wisata Sanur